HALLUX VALGUS : LICKS AT THE ANKLE JOINTS, BUT BITES AT THE HIP JOINTS? - L. A., UDOCHKINA; Yu. V., Khlebnikova; O.I., VORONTSOVA; Marina, Kapitonova (Avicenna Tajik State Medical University, 2023)
Objective: To present the coverage in the literature of recent years of the problem of the influence of foot pathology (Hallux Valgus, HV) on the condition of the proximal and distal joints of the lower limb (LL) in a comparative aspect. Methods: Literature searches were carried out in the Web of Science, PubMed and Scopus databases as of September 1, 2023 using the keywords “hallux valgus”, “bunion”, “hip joint”, “knee joint”, “ankle joint”. The inclusion criterion was the availability of full-text articles in English. Exclusion criteria included reviews, case reports, and abstracts. Results: Along with the previously described changes in the spatiotemporal parameters of gait, kinematics of the ankle joint (AJ) with HV, recently there have been studies regarding its influence on the kinematics of the proximal segment of the knee joint, including those contributing to the development of osteoarthritis (OA) of the knee joint (KJ). At the same time, disturbances in the kinematics of the hip joint (HJ) in HV, leading to the development of pathomorphological changes in it, remain unexplored. Conclusion: HV is a common disease of the musculoskeletal system, significantly worsening the quality of life of patients and often leading to disability. While the effect of HV on foot kinematics and the joint axis has been described in some detail, its effect on the hip joint remains poorly understood. Surgical treatment does not lead to a significant improvement in the kinematics of the lower limb and pelvis, but, on the contrary, can lead to its negative dynamics not only in the operated, but also in the contralateral LL, which dictates the need to conduct research to identify clinically significant kinematic parameters of gait and proximal joints of the LL for HV and optimization of existing treatment approaches.